2013
DOI: 10.1371/journal.pone.0083431
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Follow-up Observation of the Safety, Immunogenicity, and Effectiveness of Gardasil™ in Adult Women

Abstract: BackgroundPrevious analyses from a randomized trial in women aged 24–45 have shown the quadrivalent HPV vaccine to be efficacious in the prevention of infection, cervical intraepithelial neoplasia (CIN) and external genital lesions (EGL) related to HPV 6/11/16/18 through 4 years. In this report we present long term follow-up data on the efficacy, safety and immunogenicity of the quadrivalent HPV vaccine in adult women.Methods Follow-up data are from a study being conducted in 5 sites in Colombia designed to ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(50 citation statements)
references
References 15 publications
2
47
0
Order By: Relevance
“…Younger individuals have higher GMTs induced by the vaccine, which is why we used the 35–45 year old age group to compare point estimates of post vaccine GMTs since our cohort mean age was 38.1 years. 18-21 The kinetics of antibody response to qHPV vaccine show a peak one month after the third vaccine shot and a decrease in level to a plateau at 18 months, with high GMTs maintained at 5 years post vaccine. 18 , 20-22 There are some studies assessing immunogenicity in immunosuppressed populations with most showing immunogenicity with slightly lower GMTs post vaccine than in normal individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Younger individuals have higher GMTs induced by the vaccine, which is why we used the 35–45 year old age group to compare point estimates of post vaccine GMTs since our cohort mean age was 38.1 years. 18-21 The kinetics of antibody response to qHPV vaccine show a peak one month after the third vaccine shot and a decrease in level to a plateau at 18 months, with high GMTs maintained at 5 years post vaccine. 18 , 20-22 There are some studies assessing immunogenicity in immunosuppressed populations with most showing immunogenicity with slightly lower GMTs post vaccine than in normal individuals.…”
Section: Discussionmentioning
confidence: 99%
“…This reduction of seropositivity for HPV18 by cLIA is consistent with findings in aprevious study in Colombia, which reported a 45% of seropositivity for HPV18 at month 72, nevertheless a sustained absence of disease due to HPV18, as well as due to the other HPV vaccine types was observed. 32 However, when the total IgG assay is used, the proportion of women who are seropositive for HPV18 at month 72 is substantially higher (81.5% overall). The high seronegativity rate for HPV18 deserves further evaluation to better understand the long term protection of less than 3 doses schedule.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Additionally, current vaccines protect against both HPV16 and HPV18 as well as provide cross-protection against other HPV types, particularly types 31 and 45. 13 Broadspectrum protection such as this may lower the need for subsequent screening, warrant longer screening intervals than those currently used, and offer novel prevention policies against HPV-related cancers.…”
Section: 2mentioning
confidence: 99%
“…11,12 The aim of the present study is to document the benefit of a massive HPV vaccination program within a cervical cancer-screening program to extend the HPV screening interval from five to 10 years through the prevention of 6-month persistent infection as well as the prevention of CIN2+ incidence.…”
Section: Statistical Considerationsmentioning
confidence: 99%